Status and prospects for renewable energy using wood pellets from the southeastern United States. Issue 8 (20th April 2017) - Dale, Virginia H.; Kline, Keith L.; Parish, Esther S.; Cowie, Annette L.; Emory, Robert; Malmsheimer, Robert W.; Slade, Raphael; SMITH, Charles Tattersall (Tat); Wigley, Thomas Bently (BEN); Bentsen, Niclas S.; Berndes, Göran; Bernier, Pierre; et al.
Abstract: The ongoing debate about costs and benefits of wood‐pellet based bioenergy production in the southeastern United States (SE USA) requires an understanding of the science and context influencing market decisions associated with its sustainability. Production of pellets has garnered much attention as US exports have grown from negligible amounts in the early 2000s to 4.6 million metric tonnes in 2015. Currently, 98% of these pellet exports are shipped to Europe to displace coal in power plants. We ask, 'How is the production of wood pellets in the SE USA affecting forest systems and the ecosystem services they provide?' To address this question, we review current forest conditions and the status of the wood products industry, how pellet production affects ecosystem services and biodiversity, and what methods are in place to monitor changes and protect vulnerable systems. Scientific studies provide evidence that wood pellets in the SE USA are a fraction of total forestry operations and can be produced while maintaining or improving forest ecosystem services. Ecosystem services are protected by the requirement to utilize loggers trained to apply scientifically based best management practices in planning and implementing harvest for the export market. Bioenergy markets supplement incomes to private rural landholders and provide an incentive for forest management practices that simultaneously benefit water quality and wildlife and reduce risk of fire and insect outbreaks. Bioenergy also increases the value of forest land to landowners, thereby decreasing likelihood of conversion to nonforest uses. Monitoring and evaluation are essential to verify that regulations and good practices are achieving goals and to enable timely responses if problems arise. Conducting rigorous research to understand how conditions change in response to management choices requires baseline data, monitoring, and appropriate reference scenarios. Long‐term monitoring data on forest conditions should be publicly accessible and utilized to inform adaptive management.